The Role Of Music And Young Children: The Brain Development - Yahaya, Azizi (2008)
We generally think of music as something created by humans for entertainment purposes. Without knowingly, music can make us smarter. Developing a child’s musical ability may actually improve her ability to learn and be successful at other disciplines, such as language, math and science.